Gerridae (Hemiptera: Heteroptera) from the Entomological Museum of the Universidad del Valle - POSSO-G., CARMEN ELISA; GONZÁLEZ-O., RANULFO (Revista Colombiana de Entomología, 2008)
The collection of the Entomological Museum of the Universidad del Valle has specimens from 13 families of aquatic heteropterans, which includes Gerridae, a family associated with the surface film of water in lotic and lentic habitats, freshwater, brackish water and salt water. In order to approximate the diversity and distribution of the specimens from this family represented in the museum, all the entries and determined materials were revised to the species level. In total 27 species were found, represented in the following genera: Rheumatobates (four species), Limnogonus (four species), Trepobates (four species), Telmatometra (three species), Halobates (three species), Potamobates (two species), and the genera Charmatometra, Eurygerris, Tachygerris, Brachymetra, Platygerris, Telmatometroides and Metrobates each with one species, distributed in an altitudinal corridor ranging from sea level up to 2,725 meters in elevation. We report for the first time in Colombia Metrobates amblydonti. This work represents a taxonomic contribution which complements the distribution of these genera in Colombia.